An unusual case of painless hematuria - A rare case report and review of literature - Kumari, Ajitha; Sam, Mohan P.; Philip, Sany (Journal of Pathology of Nepal, 2023)
Urachal carcinoma is a rare and  aggressive  cancer arising  from a persistent  urachus which is a remnant  of  the allantois  that extends  from blader  to umblicus.This  is   a  case report  of  urachal carcinoma in a 37 year  old male who presented  with gross painless hematuria . On radiological investigation he was  found to  have  a  tumor involving  dome of bladder and urachal remnant. Cystoscoic  biopsy  suggested carcinoma. Partial cystectomy  with enblock removal of urachus  and  umblicus  was done. On cutting  the  specimen through umblicus the  urachal remnant was  identified very well  with a tumor from distal urachus  infiltrating  into the  bladder. Histologicaly  this tumor  was  identified  as  adenocarcinoma-enteric  type  involving, urachus , bladder  and perivesical fat.